The Metaphoric and the Patriarchal in Women's Writing - Gjurgjan, Ljiljana Ina (1997)
This paper aims to explore some uses of metaphors in women's writing. By looking into some texts written by modern writers Virginia Woolf and Sylvia Plath, as well as the turn of the century American writer, Charlotte Perkins Gilman, the author examines the relation between the metaphoric and the discursive in their texts.
Projekt MZOS
ENG